ANALISIS STATISTIK PERTANDINGAN FUTSAL PADA EURO FUTSAL CHAMPIONSHIP KATEGORI CAMPUS FINAL REGIONAL SURABAYA 2024 - Zulkarnain, Iskandar; Widiawati, Prisca (JURNAL ILMU KEOLAHRAGAAN, 2025)
Futsal is a fast-paced sport with limited space for movement, where players are required to always be involved in both attack and defence. This research aims to analyse the performance of the futsal team in the Euro Futsal Championship Surabaya 2024 tournament using a descriptive statistical approach. The focus of the research is possession, shooting accuracy, and saves by the goalkeeper. Data was obtained through direct observation of the matches, recording key variables such as the number of passing, shooting, ball possession, and saves. The results of the analysis showed that the participating teams had an average ball possession of 65%, with shooting accuracy reaching 54%, and the goalkeeper made saves with a success rate of 88%. This research identified that while high ball possession provides a strategic advantage, effectiveness in finishing chances and improving shooting accuracy still needs to be improved. In addition, effective goalkeeper saves also contributed significantly to the outcome of the match. The conclusion of this study is that in order to achieve victory, it is important for futsal teams to optimise ball possession, shooting techniques, and the goalkeeper's ability to make saves. The results of this analysis can provide recommendations for the development of futsal at the campus level and improve the strategy of futsal teams in Indonesia